Knowledge and Attitude of University Students in Perak, Malaysia towards Pre-Marital Screening for Thalassaemia - Kyaw Ko Latt; Amirah Syahirah Rosdi; Farah Aisyah Md Fauadi; Irdina Adwanasuha Ismail; Maryam Jamila Ali; Nur Fatimah Azzahra; Sarah Hani Ahmad Effendi; Davinder Singh (Asian Journal of Medicine & Health Sciences, 2023)
Introduction: In Malaysia, thalassaemia is regarded as one of the important public health problems. The studies showed that a high number of children had thalassaemia as it was one of the most common autosomal recessive disorders that was genetically passed down from their parents. The lack of awareness of thalassaemia itself may have contributed to this as several mothers were unaware of their thalassaemia trait until they gave birth to a thalassaemia major child. Although thalassaemia is incurable, it is controllable with an effective prevention strategy that could decrease the percentage of affected births by approximately 95%. Therefore, this study was done to assess the knowledge, awareness, and participation of university students toward pre-marital screening for thalassaemia in Perak. Materials and Methods: This was a cross-sectional study and 333 students from eight universities in Perak State answered the online questionnaire. Multistage sampling method - quota sampling followed by convenience sampling - was used. The questionnaire was composed of 3 sections: Sociodemographic data of the participants, Knowledge on thalassaemia and Attitude towards premarital thalassaemia screening. Results: Our results highlighted the knowledge and attitude towards premarital screening of thalassemia. Majority of the respondents had a high level of knowledge (63.1%) and a high level of attitude (98.8%). A statistically significant association was found between the level of knowledge and some demographic characteristics, such as gender, the university the participants were enrolled in, level of study and their educational background. However, there was no association found between the level of attitude and the demographic features. Conclusion: Majority of the participants had a high level of knowledge on thalassaemia and a good attitude towards premarital thalassaemia screening. Moreover, the students who were studying in bachelor and masterprograms had 1.8 times the chance to have higher knowledge of thalassemia than the students from foundation and diploma programs.